Learning how to fly: life lessons for the youth - Kalam, APJ Abdul (New Delhi Rupa, 2023)
Dr. A. P. J. Abdul Kalam had a great belief in the power of the youth. He met over 21 million children and young people in India and outside and spoke to them about the power of knowledge, ambition, moral behavior and the need to bring about change in society.
Keywords: President